Pendekatan Metode Tiga Fase dalam Optimasi Masalah Rute Kendaraan dengan Varian Jenis Kendaraan dan Jenis Produk - Natalia, Christine; Silalahi, Agustinus; Khantidevi, Jessica (Metris: Jurnal Sains dan Teknologi, 2017)
SClustering is a commonly system used by the distribution company. Some consumers who are in the same location but located in two different clusters as a result of a fixed and rigid area within cluster, resulting in longer delivery time and higher cost incurred to deliver the order. The purpose of this research is to determine the optimal vehicle route using three-phase method approachthat improve the clustering system. Complexity arising from the problem of this vehicle routing includes variant types of vehicles and variants of product types. The three-phase method includes a cluster-making phase with a maximum distance between consumers within 10 kilometers, a cluster adjustment phase, and a routing phase that determine shipping routes and calculate total distribution cost. Numerical examples shows that the cost of distributing goods can be minimized, from an average of IDR 1,064,408.33 to an average of IDR 775,586.46. Thus a three-phase method may improve the clustering system by reducing distribution time and cost.